THE INFLUENCE OF ENTREPRENEURIAL SKILLS ON BUSINESS START-UP INTENTION AMONG BUMIPUTRA STUDENTS - Koe, W.L.; Krishnan, R.; Utami, S. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Entrepreneurial education has been offered to university students for years. However, to what extent the entrepreneurial skills that students obtain from entrepreneurial education affect their business start-up intention is unknown. This study was geared towards examining the influence of entrepreneurial skills, i.e.: creativity, innovation and opportunity finding (CIO) on Bumiputra students’ business start-up intention. A total of 252 Bumiputra students from a Malaysian public university were used as samples through self-administered questionnaire. Based on the analysis performed, creativity and innovation were found to positively and significantly influence Bumiputra students’ business start-up intention. Meanwhile, opportunity finding was not significant. Therefore, it is important to develop creative and innovative individuals in encouraging entrepreneurship. This study further suggests that tertiary education institutions should consider using non-classroom learning approach in conducting entrepreneurial training such as learning entrepreneurship through experiential learning. The teachers or trainers should be deemed as facilitators rather than traditional knowledge givers. Lastly, the government is urged to promote a more entrepreneur-friendly business environment.